Protective Effect of Piceatannol Against Acute Lung Injury Through Protecting the Integrity of Air-Blood Barrier and Modulating the TLR4/NF-κB Signaling Pathway Activation - Peng, Lu-Yuan; Yuan, Meng; Shi, Hai-Tao; Li, Jing-He; Song, Ke; Huang, Jiang-Ni; Yi, Peng-Fei; Fu, Ben-Dong; Shen, Hai-Qing (Frontiers in Pharmacology, 2020)
Acute lung injury (ALI) are common and complex inflammatory lung diseases with higher morbidity and mortality rate. Piceatannol (PIC), a structurally related analog of resveratrol, has anti-inflammation and anti-oxidant properties. The research was designed to explore the roles and anti-inflammatory mechanisms of PIC, a well-known spleen tyrosine kinase (Syk) inhibitor, in lipopolysaccharide (LPS)-induced ALI. Twenty-four hours after LPS challenged, mice from different treatment groups were euthanized and the bronchoalveolar lavage fluid (BALF) and lung tissue samples were collected. Then the degree of pulmonary edema, lung pathological changes, MPO activity and the production of pro-inflammatory cytokines were detected. Additionally, the mRNA expression associated with cell adhesion molecule and tight junction were analyzed through qRT-PCR, and the TLR4/NF-κB activation was examined by western blot. The results showed that PIC significantly inhibited LPS-induced lung edema, histopathological damage, MPO activity, cell infiltration and production pro-inflammatory cytokines production. Moreover, PIC notably suppressed mRNA expression associated with inflammation and cell adhesion molecules. Furthermore, treatment of PIC also alleviated LPS-induced damage of air -blood barrier indicating by reduced levels of total proteins in BALF and recuperated the expression of Occludin and ZO-1 in the lung tissues. Further research also suggested that PIC remarkably restrained the LPS-induced TLR4/NF-κB pathway activation. In conclusion, PIC may be potential to treat LPS-induced ALI via regulating air-blood barrier and TLR4/NF-κB signaling pathway activation.